Artificial Intelligence in Elementary Mathematics Education: Trends, Technologies, Impacts, and Challenges - Luthfi Nur Azizah; Farizal Tanjung Effendi (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2026)
The rapid development of digital technology has significantly influenced educational practices, including mathematics learning at the elementary level. One emerging innovation is the integration of Artificial Intelligence (AI), which offers opportunities to enhance learning through adaptive and personalized approaches. This study aims to analyze trends in the use of AI in elementary mathematics education through a literature review of recent studies. This research employs a narrative literature review method by analyzing scientific articles published between 2020 and 2025 from databases such as Google Scholar, Scopus, and ERIC. The selected articles were examined to identify types of AI technologies, instructional approaches, and their impacts on learning outcomes. The results indicate that AI is increasingly utilized in forms such as intelligent tutoring systems, adaptive learning environments, and learning analytics. These technologies contribute to improving students’ conceptual understanding, engagement, and problem-solving skills, although the overall impact tends to be moderate. Additionally, challenges such as limited infrastructure and teacher readiness remain significant concerns. In conclusion, AI has strong potential to support mathematics learning in elementary schools when integrated with appropriate pedagogical strategies. This study highlights the importance of contextual implementation and suggests further research on long-term impacts and innovative learning models.